THE DECEITFULNESS OF DR. JEKYLL IN STEVENSON’S THE STRANGE CASE OF DR. JEKYLL AND MR. HYDE: (CHARACTER ANALYSIS) - juliana Ilyas; Ceisy Wuntu; Olga Rorintulus (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2022)
This study presents the analysis of the Deceitfulness of Dr. Jekyll in Stevenson’s The Strange Case of Dr. Jekyll and Mr. Hyde. The aim of this study is to analyze the qualities and conditions of Dr. Jekyll that form his deceitfulness by using the objective approach. The method used in this research is the library research method. This method is used also as the data collection technique to get information or references dealing with the object discussed. The objective approach is used here to analyze the structural elements of this novel like character, setting, conflict, and theme to reveal the research’s object. The result shows that the novel The Strange Case of Dr. Jekyll and Mr. Hyde tells about Dr. Jekyll’s deceitfulness. The main instance of the deceitfulness of Dr. Jekyll in the novel is when he hides his real personality and when he is being a murderer. There are several reasons behind the actions of Dr. Jekyll: his strict childhood, his wrong ambition, and his bad environment.